EMERGING TECHNOLOGIES IN DIABETES MANAGEMENT: FROM CONTINUOUS GLUCOSE MONITORING (CGM) TO THE ARTIFICIAL PANCREAS (2015–2025) - Karolina Nowacka; Aleksandra Grygorowicz; Klaudia Baran; Michał Ględa; Michał Szyszka; Weronika Radecka; Weronika Kozak; Agnieszka Szreiber; Karol Grela; Kamil Jabłoński; Anna Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Over the past decade, diabetes care has undergone a profound technological transformation. Continuous glucose monitoring (CGM), intermittently scanned glucose monitoring systems (isCGM/flash), sensor-integrated insulin pumps, and hybrid closed-loop systems (“artificial pancreas”) have become central components of modern management of type 1 diabetes and are increasingly used in selected forms of insulin-treated type 2 diabetes. Objective: To present a literature review from 2015–2025 on emerging technologies in diabetes treatment—from CGM to artificial pancreas systems—with particular emphasis on clinical effectiveness, psychosocial impact, and social and health-system implications. Methods: A narrative review of the literature published between 2015 and 2025, identified through searches of PubMed/MEDLINE and the Cochrane Library, as well as leading diabetology and endocrinology journals. The review included randomized controlled trials, real-world observational studies, meta-analyses, systematic reviews, and position statements from scientific societies (ADA, EASD, ISPAD, ATTD). Results: Compared with conventional self-monitoring of blood glucose (SMBG), CGM and isCGM systems significantly reduce HbA1c levels, time spent in hypoglycaemia, and glycaemic variability, while increasing time in range (TIR). Hybrid closed-loop systems further improve TIR (often exceeding 70–75%), reduce both hypo- and hyperglycaemia, and are associated with high patient satisfaction. Telemedicine and cloud-based platforms enable remote monitoring and support new models of care. Key barriers include cost, limited reimbursement, variability in digital literacy, and inequalities in access. Conclusions: Emerging technologies—from CGM and isCGM to hybrid closed-loop systems—represent a major step toward individualized and partially automated diabetes management. To fully realize their potential, equitable access, adequate funding, structured education, and integration with digital health tools and psychosocial support are essential.